2016
DOI: 10.7566/jpsj.85.073707
|View full text |Cite
|
Sign up to set email alerts
|

Conventional s-Wave Superconductivity in BiS2-Based NdO0.71F0.29BiS2 Revealed by Thermal Transport Measurements

Abstract: Conventional s-wave superconductivity in BiS 2 -based NdO 0.71 F 0.29 BiS 2 revealed by thermal transport measurements To study the superconducting gap structure of BiS2-based layered compound NdO0.71F0.29BiS2 (T c = 5 K), we measured the thermal conductivity κ, which is a sensitive probe of low-energy quasiparticle spectrum. In the absence of a magnetic field, residual linear term in the thermal conductivity κ0/T at T → 0 is vanishingly small, indicating that the residual normal fluid, which is expected for n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…According to random phase approximation calculations, a similar FS topology can produce a d-or g-wave SC gap symmetry and hence a nodal SC gap anisotropy, and its anisotropy is similar to our results that the nodes are located at the short edge of the rectangular FSs [10,18,29]. On the other hand, magnetic penetration depth measurements and thermal transport measurements have indicated nodeless superconductivity in NdO 1−x F x BiS 2 (x = 0.3 and 0.5) [30,31]. These results may seem to be inconsistent with our results.…”
supporting
confidence: 87%
“…According to random phase approximation calculations, a similar FS topology can produce a d-or g-wave SC gap symmetry and hence a nodal SC gap anisotropy, and its anisotropy is similar to our results that the nodes are located at the short edge of the rectangular FSs [10,18,29]. On the other hand, magnetic penetration depth measurements and thermal transport measurements have indicated nodeless superconductivity in NdO 1−x F x BiS 2 (x = 0.3 and 0.5) [30,31]. These results may seem to be inconsistent with our results.…”
supporting
confidence: 87%
“…Finally, we briefly discuss the pairing symmetry of the superconductivity of the BiCh 2 -based superconductor. Many experiments are consistent with fully gapped s -wave superconductivity 26 28 , while the ARPES study found an anisotropic superconducting gap 29 . The breaking of local inversion symmetry may be a key factor in the solution of the puzzle because spin-singlet and spin-triplet superconductivity can be mixed in the local inversion symmetry breaking.…”
Section: Resultsmentioning
confidence: 64%
“…Several theoretical calculations suggest that anisotropic superconductivity, such as extended s -wave, d -wave, and g -wave states, are realised in BiCh 2 -based superconductors 22 25 . However, early-stage experimental results have reported conventional fully gapped s -wave superconductivity; thermal conductivity, specific heat, and magnetic penetration depth measurements support fully gapped s -wave superconductivity 26 28 . In contrast, an anisotropic superconducting gap was observed in a laser angle-resolved photoemission spectroscopy (ARPES) apparatus 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the mechanisms of superconductivity in the BiCh 2 -based family, the pairing mechanisms of the BiCh 2 -based superconductor family are still controversial 19 , owing to superconducting properties that are tunable by external and/or chemical pressure effects, which sometimes causes scattered results. Although earlier theoretical and experimental studies suggested conventional mechanisms with fully gapped s-wave pairing states 21 23 , recent theoretical calculations of T c indicated that a T c of an order of several K to 10 K in BiS 2 -based superconductors with a tetragonal structure cannot be explained within phonon-mediated models 24 . Furthermore, angle-resolved photoemission spectroscopy (ARPES) proposed unconventional pairing mechanisms owing to the observation of a highly anisotropic superconducting gap in NdO 0.71 F 0.29 BiS 2 25 .…”
Section: Introductionmentioning
confidence: 97%